2007
DOI: 10.1007/s12026-007-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

PIP3 pathway in regulatory T cells and autoimmunity

Abstract: Regulatory T cells (Tregs) play an important role in preventing both autoimmune and inflammatory diseases. Many recent studies have focused on defining the signal transduction pathways essential for the development and the function of Tregs. Increasing evidence suggest that T-cell receptor (TCR), interleukin-2 (IL-2) receptor (IL-2R), and co-stimulatory receptor signaling are important in the early development, peripheral homeostasis, and function of Tregs. The phosphoinositide-3 kinase (PI3K)-regulated pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 222 publications
(277 reference statements)
0
18
0
Order By: Relevance
“…PI3Kδ and PI3Kγ mediated production of PtdIns(3,4,5)P 3 has been found to be an important target in a range of inflammatory and autoimmune diseases as well as in transplantation and hematological malignancies [201, 202]. In response to various extracellular stimuli, different cellular receptors such as antigen, cytokine, or chemokine receptors activate PtdIns(3,4,5)P 3 signaling in the immune system [203]. PtdIns(3,4,5)P 3 then recruits and activates GEF for Rac and Arf GTPases, resulting in actin cytoskeletal rearrangement and directional cellular movement [204].…”
Section: Implication Of Ptdins(345)p3 Signaling In Metabolic Disordmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3Kδ and PI3Kγ mediated production of PtdIns(3,4,5)P 3 has been found to be an important target in a range of inflammatory and autoimmune diseases as well as in transplantation and hematological malignancies [201, 202]. In response to various extracellular stimuli, different cellular receptors such as antigen, cytokine, or chemokine receptors activate PtdIns(3,4,5)P 3 signaling in the immune system [203]. PtdIns(3,4,5)P 3 then recruits and activates GEF for Rac and Arf GTPases, resulting in actin cytoskeletal rearrangement and directional cellular movement [204].…”
Section: Implication Of Ptdins(345)p3 Signaling In Metabolic Disordmentioning
confidence: 99%
“…It has been suggested that PI3Kγ mediates chemotaxis in T-cells, whereas PI3Kδ is responsible for the migration of B-cells [221]. Several studies reported that both increased and decreased PtdIns(3,4,5)P 3 signaling have been associated with the development of autoimmunity, suggesting that PtdIns(3,4,5)P 3 plays a role in the regulation of the functions of T-cells [203, 222, 223]. The evidence discussed above provides information supporting the importance of PtdIns(3,4,5)P 3 signaling in immune function and diseases.…”
Section: Implication Of Ptdins(345)p3 Signaling In Metabolic Disordmentioning
confidence: 99%
“…As such, the development of PI3K isoform-specific inhibitors is currently an area of intense activity. 9,13,14 In vivo inactivation of the class IA isoform p110d has been found to reduce antigen receptor function, T H 2 cytokine production, and T H 2-mediated inflammatory reactions. [15][16][17] These studies suggest that targeting p110d might be effective for the treatment of human allergy or atopic asthma.…”
mentioning
confidence: 99%
“…9,10 Several studies showed that natural oncogenic form of PI3-Kinases caused elevation in PIP 3 levels, activation of Akt and tumor progression. 8,11,12 Some recent studies showed that PIP 3 s were degraded by the two inositol phosphatases, SHIP (SH2-containing inositol phosphatase, dephosphorylates PIP 3 at the 5 position to produce PI(3,4)-P 2 ) and PTEN (phosphatase and tensine homolog, hydrolyzes PIP 3 at the 3-position to produce PI(4,5-P 2 ).…”
Section: -8mentioning
confidence: 99%